Pre-scheduled load shutdown in microgrid utilizing computerized surveillance system - G Kanimozhi; Kanimozhi G; Umamaheswari E; Devi Mani; Anitha.R U (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The successful inclusion of microgrids for enhancement of the existing power system is laden with many challenges. Increase in demand and insufficient power generation results in power shutdown in several areas which comprises non-critical loads. The preface of Distributed Generation (DG) in power system has varied implications on the existing system. The concept proposed in this paper helps in time scheduling and load scheduling of a power system based on priority setting and time setting. The load management may also be done using IoT which enables load shedding from remote areas.